2011
DOI: 10.1007/s11483-011-9226-z
|View full text |Cite
|
Sign up to set email alerts
|

Drying of Pomegranate Arils and Selection of a Suitable Drying Model

Abstract: The drying characteristics of pomegranate arils were investigated in temperature range of 50-70°C. The increase in drying air temperature resulted in a decrease in drying time. The drying rate was found to increase with temperature, thereby reducing the total drying time. Thirteen drying models were evaluated in the kinetics research. The goodness of fit of the proposed models was evaluated by using the determination of coefficient (R 2 ), mean relative percent error (P), reduced chi-square (χ 2 ), and root me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Those results for MWVD applications were in agreement with the study conducted by Bondaruk et al (2007) who observed constant rate period during vacuum‐microwave drying of potato cubes. In addition, most of the studies reported in the literature on vacuum drying of food materials exhibited similar drying kinetics as observed in our study, namely vacuum drying process followed falling rate period without observing constant rate period (Darvishi et al, 2014; Doymaz, 2011; Surendhar, Sivasubramanian, Vidhyeswari, & Deepanraj, 2018).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Those results for MWVD applications were in agreement with the study conducted by Bondaruk et al (2007) who observed constant rate period during vacuum‐microwave drying of potato cubes. In addition, most of the studies reported in the literature on vacuum drying of food materials exhibited similar drying kinetics as observed in our study, namely vacuum drying process followed falling rate period without observing constant rate period (Darvishi et al, 2014; Doymaz, 2011; Surendhar, Sivasubramanian, Vidhyeswari, & Deepanraj, 2018).…”
Section: Resultssupporting
confidence: 86%
“…The coefficient of determination ( R 2 ), root mean square error (RMSE), Chi square ( χ 2 ) were used to estimate the degree of the concordance. Best fit was obtained when R 2 is close to one and both RMSE and χ 2 are close to zero (Doymaz, 2011). R 2 was calculated from the model curve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the food industry, drying is a conventional or industrial preservation technique. To minimize the growth of bacteria, enzymatic processes, and other biochemical activities, it is frequently utilized to reduce the moisture content and water activity of food (Doymaz, 2011;Li et al, 2016). Drying is an intricate and unsteady thermal process.…”
Section: Introductionmentioning
confidence: 99%
“…Those products may be used to add color and flavor to several foods (Bhandari et al, 2007). Moreover, a dry product has lower volume and mass, which entails lower costs with storage, packaging and transportation (Dova et al, 2007;Doymaz, 2011). In this context, using powdered tucupi to prepare a powdered condiment may represent a technological alternative to preserve and add value to tucupi.…”
Section: Introductionmentioning
confidence: 99%